VALORIZAÇÃO DOS PROFESSORES:ANÁLISE DOS PLANOS DE CARREIRA DE MUNICÍPIOS DO PARANÁ - Sobzinski, Janaína Silvana (2015)
The present dissertation has as object of study the career paths of teachers of the five municipalities of the highest IDHM and the five municipalities with the lowest IDHM of Paraná. The research objectives were: assess whether municipalities studied are in accordance with the legislation, about the career path of establishment and payment of Salary Floor National Vocational and if this ensures, in fact, the valorization of teachers; conduct comparative data between the Municipal Human Development Index (HDIM), Gross Domestic Product (GDP) and the Basic Education Development Index (IDEB) with the existence of the career plans of the state of Paraná municipalities; verify if the municipalities that have a high IDHM ensure the valorization of education professionals; establish a comparative of the career paths of the five municipalities with the highest IDHM with career plans of the five municipalities with the lower IDHM in the state of Paraná. The research is based on historical and dialectical materialism, which seeks to reveal the contradictions and appreciation of teacher education in the current form of sociability. The approach is literature and documentary, and the following documents were consulted: the LDB nº 9.394, of 1996; the Law nº 11.494 of 2007 and Decree nº 6.253 of 2007, which regulates the Fund for Maintenance and Development of Basic Education and Valorization of Education Professionals (FUNDEB); Constitutional Amendment nº 53, of 2006; the National Education Plan (PNE, 2001-2011); Development Plan of Education (PDE-2007); Law of the National Professional Salary Floor, nº 11.738, of 2008; the Public National System of formation of Magisterium Professionals, of 2008; the National Policy of Magisterium of Professional Formation of Basic Education, of 2009; Resolution nº 2, of 2009, establishing the National Guidelines for Plans Career and Remuneration of Professionals of the Magisterium of Public Basic Education; Decree nº 6.755, of 2009; the new PNE Bill, nº 103, of 2012; the new National Education Plan, established by Law 13.005, of 2014; and laws that provide for the career plans of public school teachers of the municipalities of the Paraná surveyed. We emphasize the importance of these documents to analyze the valorization of teachers. As theoretical fundamentation, we turn to authors such as: Vieira, D. (2012, 2013), Peroni (2013), Saviani (2007), Scheibe (2010), Machado (2010); Gurgel (2012); Vieira, N. (2002); Arruda (2003); Meguerditchian (2012); Ferreira (2014). From the analysis, concluded that even with the existence of standards, laws and national guidelines, the federal entities, for various reasons, have had difficulties in fulfilling them, furthermore, in municipalities with less IDHM, there is less attractive career and they remunerate less teachers. However, municipalities that occupy the first places in IDHM also do not value the teachers accordingly to their level of development, since they have low growth rate between the interstices and, in many cases, it takes many years to reach the top of the career.